2010
DOI: 10.1002/jpln.201000040
|View full text |Cite
|
Sign up to set email alerts
|

Application of the DNDC model to predict N2O emissions from sandy arable soils with differing fertilization in a long‐term experiment

Abstract: Modeling crop growth and soil N dynamics is difficult due to the complex nature of soil–plant systems. In several studies, the DNDC model has been claimed to be well‐suited for this purpose whereas in other studies applications of the model were less successful. Objectives of this study were to test a calibration and validation scheme for DNDC‐model applications to describe a field experiment with spring wheat on a sandy soil near Darmstadt (SW Germany) using different fertilizer types (either application of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 25 publications
4
15
0
2
Order By: Relevance
“…Overall, the DNDC model could simulate seasonal variations of soil microclimate very well, with correlation coefficients of 0.94 and 0.78 for soil temperature and WFPS, respectively (Figures d–i). Several studies showed that the DNDC model may not work well if WFPS is overestimated [ Ludwig et al ., ; Abdalla et al, ]. In this study, the magnitudes of the daily mean WFPS between simulated and observed were similar, while daily mean soil temperature was slightly underestimated, particularly during the high temperature and drought period (Figures g–i).…”
Section: Resultssupporting
confidence: 76%
“…Overall, the DNDC model could simulate seasonal variations of soil microclimate very well, with correlation coefficients of 0.94 and 0.78 for soil temperature and WFPS, respectively (Figures d–i). Several studies showed that the DNDC model may not work well if WFPS is overestimated [ Ludwig et al ., ; Abdalla et al, ]. In this study, the magnitudes of the daily mean WFPS between simulated and observed were similar, while daily mean soil temperature was slightly underestimated, particularly during the high temperature and drought period (Figures g–i).…”
Section: Resultssupporting
confidence: 76%
“…Further, Jungkunst discusses comparably low N 2 O emissions of Haplic Chernozems (SOC accumulation by dryness) confirmed by observations on a Chernozem in southern Germany reported in (Brümmer et al 2010). Ludwig et al (2010) determined annual N 2 O fluxes on a sandy soil with increased SOC caused by long-term application of organic fertilizer. Measured annual N 2 O fluxes did not differ significantly between plots with higher SOC level and control plots.…”
Section: Key Controls Of N 2 O Fluxes Of Cropland Soilsmentioning
confidence: 99%
“…Nitrogen dynamics directly affects crop growth, soil fertility and potential pollution problems such as NH 3 volatilization, soil acidification, increased NO 3 loads of drinking water, eutrophication of surface water and emissions of the greenhouse gas N 2 O (Ludwig et al 2011). Agriculture contributes to the increase in atmospheric N 2 O, accounting for 24% of global annual emissions (IPCC 2007).…”
mentioning
confidence: 99%